Lasers in Pediatric Dentistry: A Review Article - Ankita Sinha1, Susant Mohanty2 , Sonu Acharya3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Laser applied science has been newly introduced into the dentistry to substitute drilling. The 1st dentalexperience for pediatric patients using laser can be useful from the point of preventive & therapeuticapproach. This article approached to educate about laser physics, its components, fundamentals, mechanismof its action, applications, advantages,disadvantages, laser safety & medico-legal aspects of laser specificallyconcerning pediatric dentistry. Due to their minimal invasion, treatment by laser is well accepted by children.The use of scalpels conventionally, may produce post-operative discomfort & thus, prolonged wound healing.Being safe in use, lasers are an important in-office alternative to treat pediatric dental patients. Hence, lasersuse enhances the children’s cooperation leading to greater satisfaction by all three i.e. guardians,patient &dentist.